Implikatur Konvensional dalam Meme Arab pada Akun Instagram @asa7bess (Kajian Pragmatik) - Rizalman, Mhd.; Zaini, Hisyam (Institut Agama Islam Negeri Metro, 2025)
Memes are not only used as a means of entertainment, but memes are used as a communication medium to convey certain messages that are conveyed implicitly. This study aims to analyze Arabic memes uploaded on the @asa7bess Instagram account using Grice conventional implicature theory perspective. Type of this study is descriptive-qualitative. The data in this study are Arabic memes containing words, phrases and sentences accompanied by pictures. The data source of this study is Arabic memes found on the @asa7bess Instagram account. The data in this study was collected using the documentation method, which consists of two techniques namely the select technique and the note technique. The data analysis technique in this study refers to the stages of qualitative analysis proposed by Miles and Huberman, namely data reduction, data presentation and conclusion drawing. The results show that the memes on the Instagram account @asa7bess convey conventional implicatures that can be widely understood without the need for specific context. These implied messages appear through a combination of visual and verbal elements that reflect the norms or common knowledge of society, and are grouped into three main categories: photos of one individual with a sentence, photos of two individuals with a sentence, and photos of two individuals with a dialog